2023
DOI: 10.1001/jamanetworkopen.2022.51839
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Early Return to School Following Acute Concussion and Symptom Burden at 2 Weeks Postinjury

Abstract: ImportanceDetermining how the timing of return to school is related to later symptom burden is important for early postinjury management recommendations.ObjectiveTo examine the typical time to return to school after a concussion and evaluate whether an earlier return to school is associated with symptom burden 14 days postinjury.Design, Setting, and ParticipantsPlanned secondary analysis of a prospective, multicenter observational cohort study from August 2013 to September 2014. Participants aged 5 to 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Consistent with recent studies,39 this study found that participants who delayed their return to school experienced longer symptom duration. Each additional day of delayed return was associated with 8% lower rate of symptom resolution.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with recent studies,39 this study found that participants who delayed their return to school experienced longer symptom duration. Each additional day of delayed return was associated with 8% lower rate of symptom resolution.…”
Section: Discussionsupporting
confidence: 92%
“…The current results suggest that this likely extends to students with concussion, and aligns well with the needs of this group, for whom reassurance of recovery and social support are key components of care in neurobiopsychosocial models of concussion and recovery. Extended absences and removal from social groups are known to negatively affect student outcomes, especially in older students [ 69 ], so that embedding educational delivery in a social context, as was provided here, matches with student needs.…”
Section: Discussionmentioning
confidence: 99%
“…More recent research, however, has indicated that prolonged rest after concussion is not associated with improvement in outcomes [ 11 ]. In fact, clinical evidence has demonstrated that an early return to moderate cognitive and physical activity following a concussion is beneficial for symptom resolution and reduces the incidence of persistent post-concussion symptoms compared to prolonged rest [ 12 , 13 , 14 , 15 ]. This is just one example of how our understanding of concussion management is continuously evolving, and is an illustration of why increased precision in post-concussion care is critical to improving outcomes for patients with head injuries.…”
Section: Introductionmentioning
confidence: 99%